Queer Methods and Methodologies intersecting Queer theories and social science research - Browne, Kath; J. Nash, Catherine (Taylor & Francis, 2016)
When we first envisaged this book, we anticipated that those reflecting on queer methods and methodologies might experience similar possibilities, tensions and anxieties to those we encountered in our own work. A major impetus for producing this book was our own awareness of how often we ignored or skimmed over thinking about how some methodologies and methods might not neatly fit the 'queer' conceptual frames we use in our research.